2020
DOI: 10.1371/journal.pone.0240796
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of men’s and women’s alcohol use in agrarian, trading and fishing communities in Rakai, Uganda

Abstract: Introduction Uganda has one of the highest rates of alcohol use in sub-Saharan Africa but prevalence and correlates of drinking are undocumented in the Rakai region, one of the earliest epicenters of the HIV/AIDS epidemic in East Africa. Methods We analyzed cross-sectional data from 18,700 persons (8,690 men, 10,010 women) aged 15–49 years, living in agrarian, trading and fishing communities and participating in the Rakai Community Cohort Study (RCCS) between March 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
4
19
2
Order By: Relevance
“…In 2019, Uganda banned the consumption and sale of alcohol (45% proof) in small plastic packets due to concern for increasing alcohol abuse. Previous studies in Rakai found that fishing communities and employment as fishermen or bar/restaurant keepers were associated with higher alcohol consumption [18]. Our study further links alcohol to increased risk of hypertension in fishing communities.…”
Section: Discussionsupporting
confidence: 78%
“…In 2019, Uganda banned the consumption and sale of alcohol (45% proof) in small plastic packets due to concern for increasing alcohol abuse. Previous studies in Rakai found that fishing communities and employment as fishermen or bar/restaurant keepers were associated with higher alcohol consumption [18]. Our study further links alcohol to increased risk of hypertension in fishing communities.…”
Section: Discussionsupporting
confidence: 78%
“…We found that the prevalence of self-reported drinking during pregnancy in Rakai, Uganda, was over three times higher than the global average of alcohol use among pregnant women [ 3 ], higher than previous studies conducted among pregnant women in other regions of Uganda [ 6 , 7 ], but lower than the prevalence of alcohol use among non-pregnant women in Rakai, Uganda [ 8 ]. Correlates of alcohol use during pregnancy were Catholic religion, occupation in a restaurant or bar, higher numbers of past year sex partners, having a partner who drank before sex in the past 12 months, and experiencing IPV.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous research in Rakai, Uganda, the setting for this research, found a high prevalence of alcohol use, including 39% among all women surveyed [ 8 ] and 42% among young women [ 9 ]. However, prevalence and correlates of alcohol use among pregnant women have not been assessed in Rakai.…”
Section: Introductionmentioning
confidence: 99%
“…(2) fell over; (3) got angry; (4) got violent/got into a fight; (5) had difficulty speaking; (6) forgot some of the things that you did or that happened while you were drinking; (7) had shaking hands the next morning; (8) felt ashamed of something that you did while drinking. These items were designed to capture aspects of harmful alcohol use and proxies of alcohol dependence as described in our previous research (Wagman et al, 2020). Two of these items (items 4 and 7) were adapted measures from the Michigan Alcoholism Screening Test, a validated alcoholism screening tool (Selzer, 1971) while the remaining items were developed specifically for use in the RCCS.…”
Section: Primary Independent Variablesmentioning
confidence: 99%
“…Two-thirds of men (68.8 %) who use alcohol report engaging in heavy episodic drinking (defined as at least 60 g of pure alcohol on at least one occasion in the past 60 days) while only one-third of women (32.6 %) who drink alcohol report this same behavior (WHO, 2018). Men in Uganda are also more likely to report experiencing consequences related to their alcohol use, such as drinking on the job (Wagman et al, 2020). These gendered differences in alcohol drinking patterns are culturally ingrained and socially enforced (Breuer et al, 2019;Wolff et al, 2006).…”
Section: Introductionmentioning
confidence: 99%